CARACTERISTICI COMPARATIVE ALE ACTIVITĂŢII REFLEXE CONDIŢIONATE A ŞOBOLANILOR DE DIFERITE VÂRSTE SUB INFLUENŢA BIOMASEI TULPINILOR STREPTOMYCES MASSASPOREUS CNMN-AC-06 ȘI STREPTOMYCES FRADIAE CNMN-AC-11 - Garbuzneac, Anastasia (CEP USM, 2021)
Using male white rats, it has been revealed that feeding for a long time on the biomass of Streptomyces massasporeus CNMN-Ac-06 and Streptomyces fradiae CNMN-Ac-11 strain extracted from Moldovan soils facilitates active avoidance skill learning process in young animals and especially substantially stimulates conditioned reflex activity of young and old rats. That finding opens up certain prospects of streptomyces metabolites use with the view of maintenance of cognitive processes in the period of functions diminution.
COMPARATIVE FEATURES OF CONDITIONED REFLEX ACTIVITY IN RATS OF DIFFERENT AGES UNDER THE INFLUENCE OF THE BIOMASS OF STRAINS STREPTOMYCES MASSASPOREUS CNMN-AC-06 AND STREPTOMYCES FRADIAE CNMN-AC-11
Keywords: conditioned reflexes; streptomycetes; biomass; metabolites; neuroprotective properties